Low-density silicon dioxide aerogel coiled material and preparation method thereof
By using the composite processing of low-density composite silica airgel preliminary material and fiber membrane, the deficiencies in performance and quality of airgel membranes in the existing technology are solved, and a product with low density, high thermal insulation performance and Airgel membranes with good mechanical properties are suitable for many fields.
Patent Information
- Application Number
- CN202411466909.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to meet the higher performance and quality requirements of aerogel rolls, especially in thermal insulation properties and density.
The preliminary material of low -density composite silicon gas gel was used to immerse the fiber coils under the preliminary material under the vacuum conditions, and the low -temperature aging treatment is performed to prepare low -density silicon gas gel coil coils. The initial expected is made of silicon dioxide gel and polydopamine modified nano -nano -nano -nano -nano -nano -sanxia silica.
The prepared gas gel coils have low density, high insulation performance and good mechanical strength and toughness, and are suitable for multiple fields, including construction, industry, new energy and aerospace.
Smart Images

Figure CN119330684A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coiled materials, in particular to a low-density silica aerogel coiled material and a preparation method thereof. Background Art
[0002] Aerogel roll is a special material made of aerogel technology, which has a series of unique properties and application advantages.
[0003] Aerogel roll is a rollable waterproof sheet material that is mainly waterproof and has thermal insulation function. It is made by compounding aerogel, a lightweight solid material, with a substrate (such as fiber roll) to form a roll that is both soft and has efficient thermal insulation performance.
[0004] With the continuous improvement of global requirements for energy efficiency and environmental protection and the continuous development and innovation of new material technology, aerogel membrane as a high-performance thermal insulation material has broad market prospects and development space.
[0005] With the wide application and promotion of aerogel coils in many fields, the requirements for their performance are getting higher and higher, and accordingly, the requirements for their quality are also increasing. However, the quality of aerogel coils prepared by existing technologies is difficult to meet the growing performance requirements. Therefore, it is necessary to further improve the quality of aerogel coils to ensure that they can meet higher performance standards.
[0006] Therefore, the present invention solves the corresponding problems by providing a low-density silica aerogel coil. Summary of the invention
[0007] The purpose of the present invention is to provide a low-density silica aerogel coil to solve the deficiencies in the prior art.
[0008] The technical solution adopted by the present invention is as follows:
[0009] A low-density silica aerogel coil, wherein the low-density silica aerogel coil is obtained by subjecting a fiber coil to a low-density composite silica aerogel preliminary material to an impregnation composite treatment under vacuum conditions, and then to a low-temperature aging treatment;
[0010] The low-density composite silica aerogel preliminary material is prepared by compounding silica aerogel and polydopamine-modified nano-silicon dioxide.
[0011] As a further technical solution: the fiber coil is one of a glass fiber coil, a ceramic fiber coil, a polyimide fiber coil, a carbon fiber coil, and a pre-oxidized fiber coil.
[0012] As a further technical solution: the fiber coil has a width of 0.3-1.5 m, a length of 10-100 m, and a thickness of 25 mm.
[0013] As a further technical solution: the method for preparing the low-density composite silica aerogel preliminary material is:
[0014] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 10 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0015] Among them, the stirring speed is 550r / min;
[0016] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 50-60:5:3;
[0017] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2.5;
[0018] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 35°C, the mixture was stirred for 2 hours, and then silica sol and polydopamine-modified nano-silica were added, and the mixture was stirred for 20 minutes to obtain;
[0019] The mixing mass ratio of the deionized water and methyltriethoxysilane is 45:10-12;
[0020] The volume ratio of deionized water to silica sol is 10:1;
[0021] The mass ratio of the deionized water to the polydopamine-modified nano-silicon dioxide is 40:1-1.5;
[0022] Among them, the heat preservation stirring speed is 250r / min.
[0023] As a further technical solution: the preparation method of the polydopamine-modified nano-silica is:
[0024] First, nano-silica was added to deionized water and dispersed for 10 minutes, and then TrisHCL and dopamine hydrochloride were added in sequence, and then the pH was adjusted to 8.5 with sodium hydroxide, and the temperature was adjusted to 65°C, and the mixture was stirred in a water bath for 20 hours, and then centrifuged, filtered, washed, and vacuum dried for 22 hours to obtain polydopamine-modified nano-silica;
[0025] Among them, the stirring speed is 500r / min.
[0026] As a further technical solution: the mixing ratio of the nano-silicon dioxide and deionized water is 30-35g:220mL;
[0027] The mass ratio of the nano-silicon dioxide to TrisHCL and dopamine hydrochloride is 1:2:2.5.
[0028] As a further technical solution: the centrifugal speed is 5000r / min, and the time is 10min;
[0029] The vacuum drying temperature was 55°C.
[0030] A method for preparing a low-density silica aerogel coil comprises the following steps:
[0031] (1) Prepare the substrate: fiber coil;
[0032] (2) preparing a preliminary low-density composite silica aerogel material;
[0033] (3) Vacuum impregnation:
[0034] After mixing the fiber coil and the low-density composite silica aerogel preliminary material in a volume ratio of 1:5-6, evacuate the mixture, adjust the temperature to 60°C, keep the mixture warm for 40-50 minutes, and take out the sample;
[0035] (4) Aging:
[0036] The sample is placed at 50°C and aged for 2 days to obtain the product.
[0037] As a further technical solution: the vacuuming is to evacuate to a vacuum degree of -0.1Pa.
[0038] As a further technical solution: the aging is carried out in an air atmosphere.
[0039] Beneficial effects:
[0040] characteristic:
[0041] The aerogel coil prepared by the present invention has the characteristics of low density and high thermal insulation performance. The low-density composite silica aerogel preliminary material introduced by the present invention is a lightweight material derived from gel, and its liquid component will be replaced by air during the solidification process. Therefore, the prepared aerogel coil has extremely low density and ultra-low thermal conductivity, thereby making the prepared aerogel coil one of the excellent thermal insulation materials.
[0042] The aerogel coil prepared by the present invention can not only effectively prevent water penetration on the surface, but also maintain a certain pore structure inside, thereby significantly improving the thermal insulation effect.
[0043] The aerogel coil prepared by the present invention uses a glass fiber coil as a substrate and has high flexibility and durability. The prepared aerogel coil is not only highly flexible but also elastic, can adapt to surfaces of various complex shapes, and has a wide range of applications.
[0044] The aerogel coil prepared by the present invention does not use organic solvents during production and use, does not volatilize harmful substances, and meets environmental protection requirements.
[0045] The invention introduces polydopamine-modified nano-silica, which helps to make the particle diameter distribution in the aerogel more uniform and can effectively reduce the agglomeration phenomenon, thereby improving the overall uniformity and stability of the aerogel.
[0046] At the same time, the addition of polydopamine-modified nano-silica can optimize the pore structure of the aerogel and make its pore size distribution more reasonable, which is beneficial to reduce heat conduction and improve thermal insulation performance. At the same time, a good pore structure also helps to enhance the mechanical strength and toughness of the aerogel.
[0047] The aerogel coil prepared by the present invention can be widely used in multiple fields, including: construction field, industrial field, new energy field, aerospace field, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The figure is a flow chart of a low-density silica aerogel roll. DETAILED DESCRIPTION
[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] The following are specific embodiments
[0051] Example 1
[0052] A method for preparing a low-density silica aerogel coil comprises the following steps:
[0053] (1) Prepare the substrate: glass fiber coil, the glass fiber coil has a width of 1 m, a length of 50 m, and a thickness of 25 mm;
[0054] (2) Preparation of low-density composite silica aerogel preliminary material:
[0055] The preparation method of the preliminary material of low-density composite silica aerogel is as follows:
[0056] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 10 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0057] Among them, the stirring speed is 550r / min;
[0058] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 50:5:3;
[0059] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 35°C, the mixture was stirred for 2 hours, and then silica sol and polydopamine-modified nano-silica were added, and the mixture was stirred for 20 minutes to obtain;
[0060] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2.5;
[0061] The mixing mass ratio of the deionized water and methyltriethoxysilane is 45:10;
[0062] The volume ratio of deionized water to silica sol is 10:1;
[0063] The mass ratio of deionized water to polydopamine-modified nano-silica is 40:1;
[0064] Among them, the heat preservation stirring speed is 250r / min.
[0065] The preparation method of polydopamine modified nano-silica is as follows:
[0066] First, nano-silica was added to deionized water and dispersed for 10 minutes, and then TrisHCL and dopamine hydrochloride were added in sequence, and then the pH was adjusted to 8.5 with sodium hydroxide, and the temperature was adjusted to 65°C, and the mixture was stirred in a water bath for 20 hours, and then centrifuged, filtered, washed, and vacuum dried for 22 hours to obtain polydopamine-modified nano-silica;
[0067] Among them, the stirring speed is 500r / min.
[0068] The mixing ratio of nano-silicon dioxide and deionized water is 30g:220mL;
[0069] The mass ratio of the nano-silicon dioxide to TrisHCL and dopamine hydrochloride is 1:2:2.5.
[0070] The centrifugal speed was 5000 r / min and the time was 10 min;
[0071] The vacuum drying temperature was 55°C.
[0072] (3) Vacuum impregnation:
[0073] After mixing the glass fiber coil and the low-density composite silica aerogel preliminary material in a volume ratio of 1:5, evacuate the mixture, adjust the temperature to 60°C, keep the mixture warm for 40 minutes, and take out the sample; evacuate the mixture to a vacuum degree of -0.1Pa.
[0074] (4) Aging:
[0075] The sample is placed at 50°C and aged for 2 days to obtain the product.
[0076] The aging was performed in an air atmosphere.
[0077] Example 2
[0078] A method for preparing a low-density silica aerogel coil comprises the following steps:
[0079] (1) Prepare the substrate: glass fiber coil, the glass fiber coil has a width of 1 m, a length of 50 m, and a thickness of 25 mm;
[0080] (2) Preparation of low-density composite silica aerogel preliminary material:
[0081] The preparation method of the preliminary material of low-density composite silica aerogel is as follows:
[0082] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 10 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0083] Among them, the stirring speed is 550r / min;
[0084] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 55:5:3;
[0085] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 35°C, the mixture was stirred for 2 hours, and then silica sol and polydopamine-modified nano-silica were added, and the mixture was stirred for 20 minutes to obtain;
[0086] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2.5;
[0087] The mixing mass ratio of the deionized water and methyltriethoxysilane is 45:11;
[0088] The volume ratio of deionized water to silica sol is 10:1;
[0089] The mass ratio of deionized water to polydopamine-modified nano-silicon dioxide is 40:1.2;
[0090] Among them, the heat preservation stirring speed is 250r / min.
[0091] The preparation method of polydopamine modified nano-silica is as follows:
[0092] First, nano-silica was added to deionized water and dispersed for 10 minutes, and then TrisHCL and dopamine hydrochloride were added in sequence, and then the pH was adjusted to 8.5 with sodium hydroxide, and the temperature was adjusted to 65°C, and the mixture was stirred in a water bath for 20 hours, and then centrifuged, filtered, washed, and vacuum dried for 22 hours to obtain polydopamine-modified nano-silica;
[0093] Among them, the stirring speed is 500r / min.
[0094] The mixing ratio of nano-silicon dioxide and deionized water is 32g:220mL;
[0095] The mass ratio of the nano-silicon dioxide to TrisHCL and dopamine hydrochloride is 1:2:2.5.
[0096] The centrifugal speed was 5000 r / min and the time was 10 min;
[0097] The vacuum drying temperature was 55°C.
[0098] (3) Vacuum impregnation:
[0099] After mixing the glass fiber coil and the low-density composite silica aerogel preliminary material in a volume ratio of 1:5.3, evacuate the mixture, adjust the temperature to 60°C, keep the mixture warm for 45 minutes, and take out the sample; evacuate the mixture to a vacuum degree of -0.1Pa.
[0100] (4) Aging:
[0101] The sample is placed at 50°C and aged for 2 days to obtain the product.
[0102] The aging was performed in an air atmosphere.
[0103] Example 3
[0104] A method for preparing a low-density silica aerogel coil comprises the following steps:
[0105] (1) Prepare the substrate: glass fiber coil, the glass fiber coil has a width of 1 m, a length of 50 m, and a thickness of 25 mm;
[0106] (2) Preparation of low-density composite silica aerogel preliminary material:
[0107] The preparation method of the preliminary material of low-density composite silica aerogel is as follows:
[0108] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 10 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0109] Among them, the stirring speed is 550r / min;
[0110] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 55:5:3;
[0111] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 35°C, the mixture was stirred for 2 hours, and then silica sol and polydopamine-modified nano-silica were added, and the mixture was stirred for 20 minutes to obtain;
[0112] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2.5;
[0113] The mixing mass ratio of the deionized water and methyltriethoxysilane is 45:12;
[0114] The volume ratio of deionized water to silica sol is 10:1;
[0115] The mass ratio of deionized water to polydopamine-modified nano-silicon dioxide is 40:1.3;
[0116] Among them, the heat preservation stirring speed is 250r / min.
[0117] The preparation method of polydopamine modified nano-silica is as follows:
[0118] First, nano-silica was added to deionized water and dispersed for 10 minutes, and then TrisHCL and dopamine hydrochloride were added in sequence, and then the pH was adjusted to 8.5 with sodium hydroxide, and the temperature was adjusted to 65°C, and the mixture was stirred in a water bath for 20 hours, and then centrifuged, filtered, washed, and vacuum dried for 22 hours to obtain polydopamine-modified nano-silica;
[0119] Among them, the stirring speed is 500r / min.
[0120] The mixing ratio of nano-silicon dioxide and deionized water is 32g:220mL;
[0121] The mass ratio of the nano-silicon dioxide to TrisHCL and dopamine hydrochloride is 1:2:2.5.
[0122] The centrifugal speed was 5000 r / min and the time was 10 min;
[0123] The vacuum drying temperature was 55°C.
[0124] (3) Vacuum impregnation:
[0125] After mixing the glass fiber coil and the low-density composite silica aerogel preliminary material in a volume ratio of 1:5-6, evacuate the mixture, adjust the temperature to 60°C, keep the mixture warm for 45 minutes, and take out the sample; evacuate the mixture to a vacuum degree of -0.1Pa.
[0126] (4) Aging:
[0127] The sample is placed at 50°C and aged for 2 days to obtain the product.
[0128] The aging was performed in an air atmosphere.
[0129] Example 4
[0130] A method for preparing a low-density silica aerogel coil comprises the following steps:
[0131] (1) Prepare the substrate: glass fiber coil, the glass fiber coil has a width of 1 m, a length of 50 m, and a thickness of 25 mm;
[0132] (2) Preparation of low-density composite silica aerogel preliminary material:
[0133] The preparation method of the preliminary material of low-density composite silica aerogel is as follows:
[0134] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 10 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0135] Among them, the stirring speed is 550r / min;
[0136] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 58:5:3;
[0137] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 35°C, the mixture was stirred for 2 hours, and then silica sol and polydopamine-modified nano-silica were added, and the mixture was stirred for 20 minutes to obtain;
[0138] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2.5;
[0139] The mixing mass ratio of the deionized water and methyltriethoxysilane is 45:11;
[0140] The volume ratio of deionized water to silica sol is 10:1;
[0141] The mass ratio of deionized water to polydopamine-modified nano-silicon dioxide is 40:1.35;
[0142] Among them, the heat preservation stirring speed is 250r / min.
[0143] The preparation method of polydopamine modified nano-silica is as follows:
[0144] First, nano-silica was added to deionized water and dispersed for 10 minutes, and then TrisHCL and dopamine hydrochloride were added in sequence, and then the pH was adjusted to 8.5 with sodium hydroxide, and the temperature was adjusted to 65°C, and the mixture was stirred in a water bath for 20 hours, and then centrifuged, filtered, washed, and vacuum dried for 22 hours to obtain polydopamine-modified nano-silica;
[0145] Among them, the stirring speed is 500r / min.
[0146] The mixing ratio of nano-silicon dioxide and deionized water is 34g:220mL;
[0147] The mass ratio of the nano-silicon dioxide to TrisHCL and dopamine hydrochloride is 1:2:2.5.
[0148] The centrifugal speed was 5000 r / min and the time was 10 min;
[0149] The vacuum drying temperature was 55°C.
[0150] (3) Vacuum impregnation:
[0151] After mixing the glass fiber coil and the low-density composite silica aerogel preliminary material in a volume ratio of 1:5-6, evacuate the mixture, adjust the temperature to 60°C, keep the mixture warm for 45 minutes, and take out the sample; evacuate the mixture to a vacuum degree of -0.1Pa.
[0152] (4) Aging:
[0153] The sample is placed at 50°C and aged for 2 days to obtain the product.
[0154] The aging was performed in an air atmosphere.
[0155] Example 5
[0156] A method for preparing a low-density silica aerogel coil comprises the following steps:
[0157] (1) Prepare the substrate: glass fiber coil, the glass fiber coil has a width of 1 m, a length of 50 m, and a thickness of 25 mm;
[0158] (2) Preparation of low-density composite silica aerogel preliminary material:
[0159] The preparation method of the preliminary material of low-density composite silica aerogel is as follows:
[0160] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 10 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0161] Among them, the stirring speed is 550r / min;
[0162] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 60:5:3;
[0163] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 35°C, the mixture was stirred for 2 hours, and then silica sol and polydopamine-modified nano-silica were added, and the mixture was stirred for 20 minutes to obtain;
[0164] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2.5;
[0165] The mixing mass ratio of the deionized water and methyltriethoxysilane is 45:12;
[0166] The volume ratio of deionized water to silica sol is 10:1;
[0167] The mass ratio of deionized water to polydopamine-modified nano-silica is 40:1.5;
[0168] Among them, the heat preservation stirring speed is 250r / min.
[0169] The preparation method of polydopamine modified nano-silica is as follows:
[0170] First, nano-silica was added to deionized water and dispersed for 10 minutes, and then TrisHCL and dopamine hydrochloride were added in sequence, and then the pH was adjusted to 8.5 with sodium hydroxide, and the temperature was adjusted to 65°C, and the mixture was stirred in a water bath for 20 hours, and then centrifuged, filtered, washed, and vacuum dried for 22 hours to obtain polydopamine-modified nano-silica;
[0171] Among them, the stirring speed is 500r / min.
[0172] The mixing ratio of nano-silicon dioxide and deionized water is 35g:220mL;
[0173] The mass ratio of the nano-silicon dioxide to TrisHCL and dopamine hydrochloride is 1:2:2.5.
[0174] The centrifugal speed was 5000 r / min and the time was 10 min;
[0175] The vacuum drying temperature was 55°C.
[0176] (3) Vacuum impregnation:
[0177] After mixing the glass fiber coil and the low-density composite silica aerogel preliminary material in a volume ratio of 1:6, evacuate the mixture, adjust the temperature to 60°C, keep the mixture warm for 50 minutes, and take out the sample; evacuate the mixture to a vacuum degree of -0.1Pa.
[0178] (4) Aging:
[0179] The sample is placed at 50°C and aged for 2 days to obtain the product.
[0180] The aging was performed in an air atmosphere.
[0181] Comparative Example 1:
[0182] Based on the technical solution of Example 1, polydopamine-modified nano-silica is not added, and the rest of the technical solutions remain unchanged.
[0183] Comparative Example 2:
[0184] On the basis of the technical solution of Example 1, the polydopamine-modified nano-silica was replaced with untreated nano-silica, and the rest of the technical solutions remained unchanged.
[0185] test:
[0186] Density test was performed on the samples in the example, referring to GB / T13477.2-2002:
[0187] Table 1
[0188] <![CDATA[Density kg / m 3 > Example 1 103.6 Example 2 104.1 Example 3 104.9 Example 4 105.2 Example 5 105.8
[0189] It can be seen from Table 1 that the aerogel coil prepared by the present invention has a lower density.
[0190] The thermal conductivity of the samples of the embodiment and the comparative example was tested according to ASTM D5470.
[0191] Five samples were measured in each group, and the average results are shown in Table 2:
[0192] Table 2
[0193] Thermal conductivity W / (m·K) Example 1 0.015 Example 2 0.013 Example 3 0.012 Example 4 0.015 Example 5 0.016 Comparative Example 1 0.148 Comparative Example 2 0.089
[0194] It can be seen from Table 2 that the silica aerogel coil prepared in the present invention has a lower thermal conductivity.
[0195] The water absorption rate of each group of the embodiment and the comparative example was tested:
[0196] Table 3
[0197] Water absorption % Example 1 0.57 Example 2 0.63 Example 3 0.61 Example 4 0.58 Example 5 0.59 Comparative Example 1 0.97 Comparative Example 2 0.95
[0198] It can be seen from Table 3 that the silica aerogel prepared in the present invention has a lower water absorption rate.
[0199] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.
Claims
1. A low-density silica aerogel coil, characterized in that: The low-density silica aerogel coil is obtained by subjecting the fiber coil to a low-density composite silica aerogel preliminary material to an impregnation and composite treatment under vacuum conditions, and then to a low-temperature aging treatment; The low-density composite silica aerogel preliminary material is prepared by compounding silica aerogel and polydopamine-modified nano-silicon dioxide.
2. A low-density silica aerogel coil according to claim 1, characterized in that: The fiber coil is one of a glass fiber coil, a ceramic fiber coil, a polyimide fiber coil, a carbon fiber coil, and a pre-oxidized fiber coil.
3. The low-density silica aerogel coil according to claim 1, characterized in that: The fiber coil has a width of 0.3-1.5 m, a length of 10-100 m, and a thickness of 25 mm.
4. The low-density silica aerogel coil according to claim 1, characterized in that: The method for preparing the low-density composite silica aerogel preliminary material is as follows: First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 10 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution; Among them, the stirring speed is 550r / min; The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 50-60:5:3; Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 35°C, the mixture was stirred for 2 hours, and then silica sol and polydopamine-modified nano-silica were added, and the mixture was stirred for 20 minutes to obtain; The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2.5; The mixing mass ratio of the deionized water and methyltriethoxysilane is 45:10-12; The volume ratio of deionized water to silica sol is 10:1; The mass ratio of the deionized water to the polydopamine-modified nano-silicon dioxide is 40:1-1.5; Among them, the heat preservation stirring speed is 250r / min.
5. A low-density silica aerogel coil according to claim 4, characterized in that: The preparation method of the polydopamine-modified nano-silica is as follows: First, nano-silica was added to deionized water and dispersed for 10 minutes, and then TrisHCL and dopamine hydrochloride were added in sequence, and then the pH was adjusted to 8.5 with sodium hydroxide, and the temperature was adjusted to 65°C, and the mixture was stirred in a water bath for 20 hours, and then centrifuged, filtered, washed, and vacuum dried for 22 hours to obtain polydopamine-modified nano-silica; Among them, the stirring speed is 500r / min.
6. The low-density silica aerogel coil according to claim 5, characterized in that: The mixing ratio of the nano-silicon dioxide and deionized water is 30-35 g: 220 mL; The mass ratio of the nano-silicon dioxide to TrisHCL and dopamine hydrochloride is 1:2:2.
5.
7. The low-density silica aerogel coil according to claim 5, characterized in that: The centrifugal speed is 5000r / min and the time is 10min; The vacuum drying temperature was 55°C.
8. A method for preparing a low-density silica aerogel coil according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Prepare the substrate: fiber coil; (2) preparing a preliminary low-density composite silica aerogel material; (3) Vacuum impregnation: After mixing the fiber coil and the low-density composite silica aerogel preliminary material in a volume ratio of 1:5-6, evacuate the mixture, adjust the temperature to 60°C, keep the mixture warm for 40-50 minutes, and take out the sample; (4) Aging: The sample is placed at 50°C and aged for 2 days to obtain the product.
9. The method for preparing a low-density silica aerogel coil according to claim 8, characterized in that: The vacuuming is to evacuate to a vacuum degree of -0.1Pa.
10. The method for preparing a low-density silica aerogel coil according to claim 1, characterized in that: The aging is performed in an air atmosphere.